Dampak Perang di Berbagai Wilayah Dunia terhadap Perdagangan Internasional Indonesia - Yuniarti, Tika (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Wars in various parts of the world, such as the Russia-Ukraine conflict, tensions in the Middle East, and trade wars between major countries, have had a significant impact on the global economy, including Indonesia. This study aims to analyze how these conflicts affect the volume and value of Indonesia’s international trade. The method used is a descriptive quantitative approach, with secondary data obtained from Statistics Indonesia (BPS). The results of the study show that global-scale conflicts influence Indonesia’s exports and imports, particularly in strategic commodities such as oil, gas, coal, and agricultural products. Indonesia’s trade policies have also undergone adjustments due to price fluctuations and logistical barriers caused by global conflicts.